Unveiling Fieldbus Network Technology through Project-based Learning - Lucena, Samuel E. de [UNESP] (2012)
Fieldbus communications networks are a fundamental part of modern industrial automation technique. This paperwork presents an application of project-based learning (PBL) paradigm to help electrical engineering students grasp the major concepts of fieldbus networks, while attending a one-term long, elective microcontroller course.